Characterization and Evaluation of Zeolite A/Fe3O4 Nanocomposite as a Potential Adsorbent for Removal of Organic Molecules from Wastewater. (27th August 2019) - Nyankson, Emmanuel; Adjasoo, Jonas; Efavi, Johnson Kwame; Amedalor, Reuben; Yaya, Abu; Manu, Gloria Pokuaa; Asare, Kingsford; Amartey, Nii Amarkai
Abstract : In this work, zeolite (Z) and Z-Fe3 O4 nanocomposite (Z-Fe3 O4 NC) have been synthesized. The Fe3 O4 nanoparticles were synthesized using the extract from maize leaves and ferric and ferrous chloride salts and encapsulated into the zeolite framework. The nanocomposite (Z-Fe3 O4 NC) was characterized using X-ray diffractometer (XRD), Fourier-transform infrared (FT-IR) spectroscopy, energy-dispersive X-ray (EDX) spectroscopy, and scanning electron microscopy (SEM). The potential of Z-Fe3 O4 NC as an adsorbent for removing methylene blue molecules (MB) from solution was examined using UV-Vis and kinetic and equilibrium isotherm models. The adsorption data fitted best with the pseudo-second-order model and Weber and Morris model, indicating that the adsorption process was chemisorption, while the Weber and Morris described the rate-controlling steps. The intraparticle diffusion model suggests that the adsorption processes were pore and surface diffusion controlled. The Langmuir isotherm model best describes the adsorption process indicating homogeneous monolayer coverage of MB molecules onto the surface of the Z-Fe3 O4 NC. The maximum Langmuir adsorption capacity was 2.57 mg/g at 25°C. The maximum adsorption efficiency was 97.5%. After regeneration, the maximum adsorption efficiency achieved at a pH of 7 was 82.6%.